2015
DOI: 10.1002/mrc.4290
|View full text |Cite
|
Sign up to set email alerts
|

Fast acquisition of multidimensional NMR spectra of solids and mesophases using alternative sampling methods

Abstract: Unique information about the atom-level structure and dynamics of solids and mesophases can be obtained by the use of multidimensional nuclear magnetic resonance (NMR) experiments. Nevertheless, the acquisition of these experiments often requires long acquisition times. We review here alternative sampling methods, which have been proposed to circumvent this issue in the case of solids and mesophases. Compared to the spectra of solutions, those of solids and mesophases present some specificities because they us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 129 publications
(304 reference statements)
0
6
0
Order By: Relevance
“…Besides to reduce the experimental time (T exp ) of ANAD QUOSY nD experiments that required a large number of scans for each t 1 transient, a new type of data acquisition in the direction dimension t 1 as the nonuniform sampling (NUS) approaches combined with an adapted reconstruction such as the covariance (Cov) method or compressed sensing (CS) processing can be applied. [47][48][49] F I G U R E 5 Schematic description of homonuclear and heteronuclear 2 H-QUOSY 2D/3D experiments: (A) echotype schemes (Q-resolved sequences and δ-resolved), (B) COSY-type scheme (Q-COSY), (C) double quantumtype scheme (Q-DQ), (D) Heteronuclear HETCORtype sequence (CDCOM or NASDAC or 2D Refocussed-NASDAC), and (E) homonuclear 3D-type sequence (3D Q-DQ). Figure adapted from reference 23 with permission…”
Section: D Experiments Involving Spins-1/2 Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…Besides to reduce the experimental time (T exp ) of ANAD QUOSY nD experiments that required a large number of scans for each t 1 transient, a new type of data acquisition in the direction dimension t 1 as the nonuniform sampling (NUS) approaches combined with an adapted reconstruction such as the covariance (Cov) method or compressed sensing (CS) processing can be applied. [47][48][49] F I G U R E 5 Schematic description of homonuclear and heteronuclear 2 H-QUOSY 2D/3D experiments: (A) echotype schemes (Q-resolved sequences and δ-resolved), (B) COSY-type scheme (Q-COSY), (C) double quantumtype scheme (Q-DQ), (D) Heteronuclear HETCORtype sequence (CDCOM or NASDAC or 2D Refocussed-NASDAC), and (E) homonuclear 3D-type sequence (3D Q-DQ). Figure adapted from reference 23 with permission…”
Section: D Experiments Involving Spins-1/2 Nucleimentioning
confidence: 99%
“…To experimentally fight the inherent low sensibility of ANAD 2D NMR, the use of higher magnetic fields (> 9.4 T) and selective 2 H probes (standard probe or better, a cryogenic probe 46 ) is a simple way to increase the sensitivity of NAD 1D/2D experiments. Besides to reduce the experimental time ( T exp ) of ANAD QUOSY nD experiments that required a large number of scans for each t 1 transient, a new type of data acquisition in the direction dimension t 1 as the nonuniform sampling (NUS) approaches combined with an adapted reconstruction such as the covariance (Cov) method or compressed sensing (CS) processing can be applied 47–49 …”
Section: Nmr Tools Versus Magnetically Active Nucleusmentioning
confidence: 99%
“…The sensitivity of the NMR detection has been significantly increased by the introduction of Fourier Transform NMR spectroscopy [7]. More recently, the sensitivity per spin of NMR detection for solids has also been increased using techniques, such as Magic-Angle Spinning (MAS) NMR probes with cryogenic detection systems, also termed cryoprobe [8], microcoils [9] and non-uniform sampling of the indirect dimensions of multidimensional NMR experiments [10].…”
Section: Introductionmentioning
confidence: 99%
“…36a,b, respectively. In short, the analysis of these results has shown that: i) the combination of NUS-Cov allows spectral resolution to be enhanced and measurement time to be reduced by a factor of 4 with respect to US-FT and by a factor of 2 with respect to US-Cov techniques [256]; ii) for the NUS-CS schedule, it was shown that the highest spectral fidelity is obtained for T S ≈ 0.5-0.6 × T 2 * in the case of exponentially decaying NUS [257], and this sampling scheme enhances the sensitivity and resolution of anisotropic NAD 2D-NMR experiments compared to US-FT classical combination [258]. [256] and [257], with permission.…”
Section: Non-uniform Sampling and Special Processingmentioning
confidence: 91%
“…The acquisition of multidimensional NMR spectra of solutes in isotropic samples can be accelerated by various strategies. Among them, we can include for instance: i) the enhancement of the population difference across the excited transition using high magnetic field, DNP [250], low and ultralow temperatures [251] ; or polarization transfer methods [9,10,15]; ii) the use of more sensitive detection schemes through the indirect detection of abundant nuclei ( 1 H, 19 F); iii) the minimization of the recycling delay (T R ), by using band-selective 1 H or 13 on spectral resolution and sensitivity was examined [256,257,258].…”
Section: Non-uniform Sampling and Special Processingmentioning
confidence: 99%